2016
DOI: 10.1038/srep22026
|View full text |Cite
|
Sign up to set email alerts
|

Reintroduction of confiscated and displaced mammals risks outbreeding and introgression in natural populations, as evidenced by orang-utans of divergent subspecies

Abstract: Confiscated and displaced mammals are often taken to sanctuaries, where the explicit goal may be reintroduction to the wild. By inadvertently collecting animals from different source populations, however, such efforts risk reintroducing individuals that have not been in genetic contact for significant periods of time. Using genetic analyses and 44 years of data from Camp Leakey, an orang-utan rehabilitation site on Borneo, we determined the minimum extent to which orang-utans representing non-native, geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 68 publications
1
36
0
2
Order By: Relevance
“…Our results therefore highlight the fact that meiosis constitutes a specific biological obstacle to population mixture, possibly because of the involvement of a high number of speciation genes during this cellular process (Mihola, et al 2009;Nosil and Schluter 2011). These results are also consistent with the suggestion that the reproductive fitness of archaic-modern human hybrids was probably marginal, as in hybrids of genetically divergent lineages in other taxa (Rhymer and Simberloff 1996;Corbett-Detig, et al 2013;Banes, et al 2016). According to our results it is possible that reduced hybrid fertility was not restricted to males but also affected females.…”
Section: Discussionsupporting
confidence: 80%
“…Our results therefore highlight the fact that meiosis constitutes a specific biological obstacle to population mixture, possibly because of the involvement of a high number of speciation genes during this cellular process (Mihola, et al 2009;Nosil and Schluter 2011). These results are also consistent with the suggestion that the reproductive fitness of archaic-modern human hybrids was probably marginal, as in hybrids of genetically divergent lineages in other taxa (Rhymer and Simberloff 1996;Corbett-Detig, et al 2013;Banes, et al 2016). According to our results it is possible that reduced hybrid fertility was not restricted to males but also affected females.…”
Section: Discussionsupporting
confidence: 80%
“…Three update shorter sequences previously generated from the same individuals in our prior study [18], and retain their original accession codes (KU523975-KU523977). One sequence (haplotype S4) proved identical at this resolution to a published full-genome sequence in GenBank (accession code X97708; [37]), known to have derived from a different matriline.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in the case of orang-utans, it is unlikely that polymorphisms elsewhere in the control region would prove to be of taxonomic importance: studies at much higher resolutions, incorporating full mtDNA genome and nuclear-genome-wide variations, are already underway or published by other research groups, and are needed to explain the abundant idiosyncrasies observed in orang-utan taxonomy. Bornean orang-utan subspecies are known not to be reciprocally monophyletic based on mtDNA [41,45], though this may–to some extent–be the result of male dispersal or the unintentional translocation and reintroduction of non-native individuals [18,45,46]. More notably, through phylogenetic analysis of mtDNA, one Sumatran subpopulation has been shown to be more closely related to orang-utans on Borneo than to others on Sumatra [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of primate species have been successfully introduced in some places, including orangutans, lar gibbons ( Hylobates lar ), southern yellow-cheeked gibbons ( Nomascus gabriellae ), Indonesian slow lorises ( Nycticebus ), Delacour’s langurs ( Trachypithecus delacouri ), western gorillas, woolly monkeys ( Lagothrix lagotricha ), golden lion tamarins ( Leontopithecus rosalia ), and pygmy marmosets ( Cebuella pygmaea ) ( 146 – 150 ). Still, evidence of outbreeding and introgression in, for example, Bornean orangutan populations due to the reintroduction of rescued animals of different species and subspecies into wild populations highlights the care that must be taken using these kinds of conservation interventions ( 151 ). …”
Section: Addressing Conservation Needsmentioning
confidence: 99%